## Elementary Technical Mathematics

Published by Brooks Cole

# Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises - Page 242: 31

y=10

#### Work Step by Step

Simplifying y + -4 = 2(y + -7) Reorder the terms: -4 + y = 2(y + -7) Reorder the terms: -4 + y = 2(-7 + y) -4 + y = (-7 * 2 + y * 2) -4 + y = (-14 + 2y) Solving -4 + y = -14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -4 + y + -2y = -14 + 2y + -2y Combine like terms: y + -2y = -1y -4 + -1y = -14 + 2y + -2y Combine like terms: 2y + -2y = 0 -4 + -1y = -14 + 0 -4 + -1y = -14 Add '4' to each side of the equation. -4 + 4 + -1y = -14 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = -14 + 4 -1y = -14 + 4 Combine like terms: -14 + 4 = -10 -1y = -10 Divide each side by '-1'. y = 10 Simplifying y = 10

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.